The Effects of Situation Variability in a Simulation-Based Training for Implicit Innovation Knowledge. (August 2020) - Van Lysebetten, Saar; Anseel, Frederik; Sanchez, Diana R.
Background . During the last decades, the use of simulations for training purposes has sparked wide interest. However, it is unclear howtraining format characteristics may affect learning, resulting in a lack of evidence-based guidelines for training developers and organizations. Aim . We explore to what extentvariation in the situations presented during a simulation training may improve learning outcomes. We test this research question in the context of asimulation-based training for improvinginnovation knowledge . Methods . A sample of 131 business students was invited to participate in a study witha pretest and two posttests (within 48 hours after and 4 weeks later) andthree conditions : a control group without training, an experimental training group with low situational variation, and an experimental training group with high situational variation. Results and Conclusion . Compared to the control group, high but not lowsituational variation improved innovation knowledge . Participants'prior innovation knowledge did not moderate the results. Hence, our findings indicate that ideally a simulation training includes multiple situations that offer learnersvarious opportunities to practice innovation challenges.